The Influence of Perceived Quality and Perceived Risk on Online Purchase Intention in E-Commerce (Case Study of Pt Shopee Indonesia) - Sukarya, Sumiati; Kristanto, Yudi; Army, Widya Lelisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the effect of quality and perceived risk to online purchase intention on e-commerce (pt shopee indonesia case study). This research method uses quantitative data collection methods with questionnaires, the sample in this research consists of 100 shop customers. by using a probability sample, the data analysis used is correlation regression, so it is clear how big the influence is perceived of quality and perceived of risk to online purchase intention on e-commerce (pt shopee indonesia case study) results of research that examines the influence perceived of quality and perceived of risk to online purchase intention on e-commerce (pt shopee indonesia case study) significant effect amounting to 58.8% variation online purchase intention can be explained by variation perceived of quality and perceived of risk, the remaining 41.2% is determined by other outside factors perceived of quality and perceived of risk.